Media Permainan Engklek terhadap Hasil Belajar IPS Siswa Sekolah Dasar - Putri Elviana Ayu Ramadhani; Dewi Widiana Rahayu; Sunanto Sunanto; Pance Mariati (FKIP, Universitas Palangka Raya, 2024)
The background of student motivation on social studies learning outcomes for elementary school students in class learning is very important. Thus, what happened to VF class students when learning was that some of them were less enthusiastic about learning, often talked to friends when the teacher explained in front of them, fell asleep, and when given assignments they preferred to do homework. The purpose of this research is to describe media development, media feasibility, and teacher and student responses to the development of crank game media in improving social studies learning outcomes for SDN Kertajaya IV/210 Surabaya students. This research method uses the R&D (Research and Development) research method which uses the 6 initial stages of Sugiyono's development model, namely: Potential and problem stages; Data collection stage; Product design stage; Design validation stage; Design revision stage; and Product trial stage. The instrument used in this study, using a questionnaire / questionnaire and test. The results showed that students' social studies learning had increased with an average score of 63.43 to 77.18. The response of teachers and students also looks very enthusiastic when playing the learning media. Research in general shows that students' social studies learning has increased with an average score of 63.43 to 77.18. The response of teachers and students also looks very enthusiastic when playing the learning media. Thus, the hopscotch game media in learning shows the